Comparative Analysis of the Performance of Different Codecs in a Live VoIP Network using SIP Protocol - Bojovic, Z.; Peric, Z.; Delic, V.; Secerov, E.; Secujski, M.; Senk, V. (Elektronika ir Elektrotechnika, 2012)
In this paper we analyzed the impact of different codecs on the quality of VoIP services. We analyzed the performance of VoIP networks to have made an assessment to what extent are fulfilled the expectations regarding the desired quality of service and the authors applied the following methodology: we selected according to certain criteria and the same codecs implemented in a VoIP network, then selected the appropriate traffic routes and measurements carried out on them, and finally at the end is based on measurement results obtained comparative analysis and the comparisons made packet loss parameter. In the paper are discussed the main problems regarding the quality of VoIP services: and the choice of coding techniques. Measurements were performed with common used codecs for VoIP: G.711, G.723 and G.729, and the variation values of packet size and number of calls. Also, measurements were performed with optical and wireless transmission system. Finally, the main objective of this study was to select an appropriate codec to get a high quality voice and tries to compromise between price/quality of service. In conclusion, G.711 is the preferred technique that provides high voice quality (MOS greater than 4) but with a flaw need high bandwidth, and G.723 provide relatively good voice quality (MOS between 3 and 4) with a much smaller bandwidth, which means it can handle multiple users. The G.729 has a high level of compression and proper technique for many users, but only when the voice quality is not taken into account. Ill. 11, bibl. 9, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1050